Operating costs and profitability to company value - Yuliana, Shella; Fatmala, Emah; Adiansyah, Nola Putri; Haryadi, Didit; Wahyudi, Wahyudi (Trigin Publisher, 2024)
Increasing economic growth makes competition tighter in the business world, especially in the food and beverage business. This study investigates the interaction between operational costs, profitability, and company value in Indonesia's food and beverage sector. The aim is to gain insight into how these factors interact and affect the overall value of companies in the Indonesian region. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of Food and Beverages companies operating in Indonesia, as many as 24 companies, with purposive sampling techniques of 17 companies sampled for 2020 – 2022. This study examines the relationship between firm cost, profitability, and value through statistical analysis and linear regression modelling techniques with SPSS version 26. The results showed that operational expenses had a significant effect on the value of the company. Profitability has a substantial impact on the value of the company. Then, operating costs and profitability have a considerable effect on the value of the company. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to Indonesia's Food and Beverages sector. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive corporate value in the industry, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management.